Combining the Sterile Insect Technique with the Incompatible Insect Technique: III-Robust Mating Competitiveness of Irradiated Triple Wolbachia-Infected Aedes albopictus Males under Semi-Field Conditions - Zhang, Dongjing; Lees, Rosemary Susan; Xi, Zhiyong; Bourtzis, Kostas; Gilles, Jeremie R. L. (PLOS ONE, 2016)
Combination of the sterile insect technique with the incompatible insect technique is considered to be a safe approach to control Aedes albopictus populations in the absence of an accurate and scalable sex separation system or genetic sexing strain. Our previous study has shown that the triple Wolbachia-infected Ae. albopictus strain (wAlbA, wAlbB and wPip) was suitable for mass rearing and females could be completely sterilized as pupae with a radiation dose of at least 28 Gy. However, whether this radiation dose can influence the mating competitiveness of the triple infected males was still unknown. In this study we aimed to evaluate the effects of irradiation on the male mating competitiveness of the triple infected strain under laboratory and semi-field conditions. The results herein indicate that irradiation with a lower, female-sterilizing dose has no negative impact on the longevity of triple infected males while a reduced lifespan was observed in the wild type males (wAlbA and wAlbB) irradiated with a higher male-sterilizing dose, in small cages. At different sterile: fertile release ratios in small cages, triple-infected males induced 39.8, 81.6 and 87.8% sterility in a wild type female population at 1:1, 5:1 and 10:1 release ratios, respectively, relative to a fertile control population. Similarly, irradiated triple infected males induced 31.3, 70.5 and 89.3% sterility at 1:1, 5:1 and 10:1 release ratios, respectively, again relative to the fertile control. Under semi-field conditions at a 5:1 release ratio, relative to wild type males, the mean male mating competitiveness index of 28 Gy irradiated triple-infected males was significantly higher than 35 Gy irradiated wild type males, while triple infected males showed no difference in mean mating competitiveness to either irradiated triple-infected or irradiated wild type males. An unexpected difference was also observed in the relative male mating competitiveness of the triple infected strain after irradiation at 28 Gy dose in small vs large cages, with a higher male mating competitiveness index calculated from results of experiments in the large cages. Based on these results, we consider that the male mating performance of the triple infected strain after irradiation at 28 Gy, a dose required for complete female sterility and the avoidance of population replacement, is approximately equal to that of the wild type males under semi-field conditions. Though field evaluation is required, this suggests that the triple infected strain is suitable for irradiation and release as part of a combined SIT-IIT approach to Ae. albopictus control.